2019
DOI: 10.6018/cpd.340741
|View full text |Cite
|
Sign up to set email alerts
|

Dimensões de Burnout, Estratégias de Coping e Tempo de Prática como Atleta Federado em Jogadores Profissionais de Futebol

Abstract: El objetivo del estudio consiste en investigar las siguientes correlaciones bivariadas en jugadores profesionales de fútbol: a) dimensiones de agotamiento x estrategia de afrontamiento; b) tiempo de práctica como atleta federado x dimensiones de agotamiento; c) tiempo de práctica como atleta federado x estrategias de afrontamiento. Participaron del estudio 54 atletas profesionales Brasileños de fútbol de la primera división del Campeonato Paraense de 2018, todos del sexo masculino. El promedio de edad fue de 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
7
0
4
Order By: Relevance
“…In general, the results showed that during the soccer sports season, seven athletes (13.20%) presented high levels of frequency of feelings of burnout during the 3 periods evaluated (Table 2). When comparing this result with the few findings in the literature that analyzed burnout individually in athletes, it was observed that the results are very similar in relation to the percentage of athletes affected with high levels of burnout 21,27,28 .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In general, the results showed that during the soccer sports season, seven athletes (13.20%) presented high levels of frequency of feelings of burnout during the 3 periods evaluated (Table 2). When comparing this result with the few findings in the literature that analyzed burnout individually in athletes, it was observed that the results are very similar in relation to the percentage of athletes affected with high levels of burnout 21,27,28 .…”
Section: Discussionsupporting
confidence: 59%
“…Pires et al 27 and Hill et al 28 evaluated burnout in soccer athletes and indicated that although most of the athletes analyzed presented moderate to low levels for the dimensions of burnout, considering the values of the dimension Reduced Sense of Sports Achievement and Physical and Emotional Exhaustion, a small percentage of athletes could be exhibiting more extreme thoughts and feelings related to the syndrome. De Francisco et al 14 evaluated 442 athletes from 34 sports and indicated a mean level of frequency of feelings of 2.18 for total burnout and a percentage ranging from 3.4 to 3.8% of athletes manifesting the syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this context, several studies have been conducted to analyse burnout in Brazilian football 13,15,16 . Some findings in this context have identified that coping strategies are developed as an athlete's experience increases since the athlete is exposed to different sources of stress throughout his career; athletes are thus capable of developing problem-focused strategies that can mitigate or prevent high-burnout indicators 17 . Another study found that the variables of amotivation and overtraining can predict burnout in professional football players 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the present study aims to investigate the indicators of burnout to assess whether the variable of playing position affects the perception of burnout dimensions and to identify burnout prevalence in professional football players. First, we hypothesized that athletes would have low indicators of burnout dimensions as evidenced in previous studies of football players 15,17 . Second, we expected to find a difference in the perception of burnout dimensions according to the variable of playing position.…”
Section: Introductionmentioning
confidence: 99%